From Danish Cartoons to Norway's Anders Breivik: Secularism and Perceptions of Muslims in Scandinavian Social Imaginaries - Veninga, Jennifer Elisa (Journal of religion & society. Supplement, 2018)
Over twelve years have passed since the Danish newspaper Jyllands-Posten published a series of cartoons of the Prophet Muhammed, an event which brought Denmark into the global spotlight and triggered protests around the world. Almost seven years ago, another Scandinavian nation was drawn into crisis when Anders Behring Breivik murdered 77 fellow Norwegians in what he believed to be an effort to resist the “Islamic colonisation of Europe.” This article argues that both events revealed particular conceptions of what it means to be fully human in a modern secular democracy, and according to this framework, Muslims do not meet these criteria. To examine this claim, the article first considers the perception of Muslims and immigrants as a threat to the secular social imaginaries of these societies, and then analyzes the nature of the “moral injury” experienced by Muslims and the corresponding unintelligibility of those injuries in these contexts.